2016
DOI: 10.1002/bdra.23480
|View full text |Cite
|
Sign up to set email alerts
|

Measuring self‐reported quality of life in 8‐ to 11‐year‐old children born with gastroschisis: Is the KIDSCREEN questionnaire acceptable?

Abstract: The KIDSCREEN questionnaire has adequate face and content validity as a measure of QoL in children with gastroschisis and is acceptable to both children and parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
(47 reference statements)
1
2
0
Order By: Relevance
“…In comparison with our study, previous literature showed overall health status in line with normative expectations [5, 2830]. Our study showed that children with gastroschisis had slightly lower scores on the school functioning subscale of the PedsQL than their matched controls.…”
Section: Discussionsupporting
confidence: 86%
“…In comparison with our study, previous literature showed overall health status in line with normative expectations [5, 2830]. Our study showed that children with gastroschisis had slightly lower scores on the school functioning subscale of the PedsQL than their matched controls.…”
Section: Discussionsupporting
confidence: 86%
“…Rankin et al reported that children with gastroschisis had similar QoL compared with age-matched children from a background population at the age of 8-11 years, yet this study suffered from small sample size. 16 Another larger study showed that simple and complicated gastroschisis patients have similar quality of life after the age of two years compared to healthy children, which is reassuring when counseling the parents. 17…”
Section: Need For Surgery In Childhood and Adolescencementioning
confidence: 94%
“…The literature search on QoL measures that had been used in gastroschisis yielded 9 papers published from 2010 in which QoL had been reported. Of these, 6 had used the PedsQL score[ 47 – 52 ] two had used the KIDCSREEN instrument [ 53 , 54 ] and one had used an unvalidated scoring system [ 55 ].…”
Section: Volume/outcome Relationshipmentioning
confidence: 99%